Investigating the Influence of E-HRM Practices on Organizational Performance: The Mediating Role of Organizational Agility (With Special Reference to Financial Institution) - A .D .S .Thathsara; Jayaranjani Sutha (International Journal of Engineering and Management Research, 2021)
Electronic Human Resource Management (E-HRM) came into existence as a result of the evolution of new technology and it leads to eliminating the administrative burden on HR professionals. Financial institutions are the heart of the financial stability of the economy. Nowadays most financial institutions are widely adopting E-HRM practices in order to achieve sustainable competitive advantage. However, it has been observed that there is a lack of empirical studies regarding this phenomenon in the Sri Lankan context. The main contribution of this study is to enrich the knowledge and investigate the impact of E-HRM practices on organizational performance under the mediation role of organizational agility. Thus, the study focusses on to examine how E-HRM impacts organizational performance, and to determine the mediating role of organizational agility between E-HRM and OP. Questionnaires were distributed by using a convenience sampling method to collect primary data from 40 financial institutions in Sri Lanka. Data analysis was performed using Pearson correlation analysis, regression analysis, descriptive statistics, Baron and Kenny mediator analysis method, and Sobel test. Results of the analysis indicated that E-HRM practices significantly and positively impact organizational performance while organizational agility mediates the relationship between E-HRM practices and OP. Outcomes of this study provided implications like enhancing available literature, to understand the real impact of E-HRM on organizational performance to HR managers. This study also suggests some further research areas for future research.